Postoperative antibiotic therapy patterns in Benign Prostatic Hyperplasia (BPH) patients - Aghnia Fuadatul Inayah; Rizki Lisya Nugraha; Didik Hasmono (Universitas Muhammadiyah Malang, 2020)
Benign Prostatic Hyperplasia (BPH) is an enlarged prostate disease benign or a condition when the cells are present the prostate gland has an increased proliferation rate. There are several treatment options, including conservative (watchful waiting), medical, and surgery. Antibiotics in BPH cases can be prophylactic antibiotics or empiric antibiotics. This study was an observational study. The samples were BPH patients who received antibiotics for period January - November 2019. The pattern of prophylactic antibiotic use shows that most of the patients received ceftriaxone therapy. Operation on BPH patients is TURP which is an operation classified into surgery with a clean-contaminated category so that prophylactic antibiotics are required. There are two patterns of use for empiric antibiotics in BPH patients: single (88%) and combination (12%). The pattern of single or combined use is given to patients depending on the complications of the disease and the patient's clinical condition. BPH cases occur in men mostly occurs at the age of 60-74 years. Prophylactic antibiotic therapy in BPH patients, namely ceftriaxone 1 gr IV once daily was 48 patients (90.6%), a broad spectrum. Meanwhile, the most use of empirical antibiotics with a single pattern is Ceftriaxone 1 gr IV twice daily (35.6%).